2020
DOI: 10.21861/hgg.2020.82.02.04
|View full text |Cite
|
Sign up to set email alerts
|

The potential of memorial tourism development in Istria (Croatia)

Abstract: This paper analyses the geographical features and potential of memorial tourism development in the tourism region of Istria in Croatia. In the past century, Istria has had several political and socio-economic turning points, with far-reaching consequences for its overall development. For the most part, the historical turning points in the 20th century in Istria were marked by armed conflict, followed by individual and mass human casualties, terror, and the persecution of the population. The motive of travel in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…By considering the media perspective of memorial events, WWI-related memorial practices, and their relation to dark tourism, this research provides a new understanding of Istrian memorial events, which, however, cannot always be included in the dark tourism context; this is, after all, consistent with the claims of Kennell et al (2018), because local communities understand/experience these events/processes in their own way (Dolenec & Vodeb, 2022;Kavrečič & Hrobat Virloget, 2019;Vojnović, 2020). This research thus showed the local and wider scope of memorial events in the region marked by tourism.…”
Section: Further Discussion and Tourism Implicationsmentioning
confidence: 79%
See 4 more Smart Citations
“…By considering the media perspective of memorial events, WWI-related memorial practices, and their relation to dark tourism, this research provides a new understanding of Istrian memorial events, which, however, cannot always be included in the dark tourism context; this is, after all, consistent with the claims of Kennell et al (2018), because local communities understand/experience these events/processes in their own way (Dolenec & Vodeb, 2022;Kavrečič & Hrobat Virloget, 2019;Vojnović, 2020). This research thus showed the local and wider scope of memorial events in the region marked by tourism.…”
Section: Further Discussion and Tourism Implicationsmentioning
confidence: 79%
“…Pula, as the centre of Croatian Istria with clear military history and connection with WWI (Herman Kaurić, 2015b; Mandić, 2006;Vojnović, 2020), implemented the Puna je Pula project (Obilježavanje stogodišnjice Prvog svjetskog rata, n.d.), which included 30 different events related to WWI (articles C, J, O). In the nearby Municipality of Ližnjan, in connection to the centenary of WWI and the sinking of the ship "Cesare Rossarol", "The Wreck of the Warship Cesare Rossarol" project was implemented, consisting of cultural, tourist-recreational, religious, educational, and audiovisual events with memorial significance.…”
Section: Discussion On Memorial Events In the Cross-border Region Of ...mentioning
confidence: 99%
See 3 more Smart Citations